A new map of the Northern States containing the Kingdoms of Sweden, Denmark, and Norway; with the western parts of Russia, Livonia, Courland & ca. - Kitchin, Thomas (London: printed for Robert Sayer, 1788, 1788)
0-meridiaani: Ferro: Koordinaattiasteikko: E5°-65°, N72°-53°.
Keywords: 1780-luku; Suomi; Ruotsi; Norja; Tanska; Pohjois-Eurooppa; kartat